PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN KERAJINAN PADA SULAMAN INDAH MITRA DI DESA NARAS 1 KOTA PARIAMAN - Nurtati; Febriani Fitri; Dedi Mardianto (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2021)
This type of research is descriptive and quantitative, because this research is used to provide an objective description or description of a situation. This study aims to see the effect of market orientation on marketing performance, the effect of product innovation on marketing performance and to see the effect of market orientation and product innovation on marketing performance. This research was conducted in the form of interviews and questionnaires. The population in this study were all women in Naras 1 village, amounting to 593 people for the age group 25 to 59 years. The sample in this study were 59 people, where the sampling technique used accidental sampling method. This study uses hypothesis testing. The results of this study indicate that partially market orientation has no significant effect on marketing performance because the value of thit <ttab (1.303 <1.6715) and product innovation has a significant effect on marketing performance because thit> ttab (8.132 > 1.6715). Meanwhile, simultaneously market orientation and product innovation have a significant effect on marketing performance because fhit> ftab (37.685> 1.6715). Based on the results of the Determination (R2) test, the contribution of the independent variables of Market Orientation (X1) and Product Innovation (X2) to Marketing Performance (Y) is 57.4%, This shows that the influence between the two variables is very strong because the greater the Rsquare number the stronger the effect between the two variables.